Implementasi dan Inovasi Penguatan Kurikulum MBKM Berorientasi OBE Pada Prodi Akuntansi Syariah - Aulia Azimi; Heny Hidayati; Fitri Jayanti (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
Abstract The implementation of a curriculum will be drawn from internal and external users, for this reason, an innovation strategy is needed to strengthen the MBKM curriculum so that it is implemented with principles according to the needs of graduates and the world of work. Needs analysis was carried out through FGD and the results of the socialization of the OBE-oriented MBKM curriculum. The method used in this study is service learning, which is a combination of academic material with community service. The results of this study are: 1) The Focus Group Discussion (FGD) activity succeeded in exploring the needs and readiness of lecturers, students, alumni and stakeholders for the OBE-oriented MBKM curriculum. 2) Phase 1 & 2 socialization activities received a good response from the socialization participants, the OBE-oriented MBKM curriculum has been described from the distribution of courses that are in accordance with the needs of the world of work and the implementation of MBKM implementation of the Sharia Accounting study program has been carried out, but it still needs to be strengthened by coming up with a strategy in the form of innovations to strengthen the MBKM curriculum that is more adaptable and collaborative with the industrial world. From the results of this research, it is hoped that the curriculum of the study program will be realized according to the needs of graduates and internal and external users.